Former food products safety: microbiological quality and computer vision evaluation of packaging remnants contamination. Issue 8 (3rd August 2017) - Tretola, M.; Di Rosa, A. R.; Tirloni, E.; Ottoboni, M.; Giromini, C.; Leone, F.; Bernardi, C. E. M.; Dell'Orto, V.; Chiofalo, V.; Pinotti, L.
ABSTRACT: The use of alternative feed ingredients in farm animal's diets can be an interesting choice from several standpoints, including safety. In this respect, this study investigated the safety features of selected former food products (FFPs) intended for animal nutrition produced in the framework of the IZS PLV 06/14 RC project by an FFP processing plant. Six FFP samples, both mash and pelleted, were analysed for the enumeration of total viable count (TVC) (ISO 4833), Enterobacteriaceae (ISO 21528-1), Escherichia coli (ISO 16649-1), coagulase-positive Staphylococci (CPS) (ISO 6888), presumptive B acillus cereus and its spores (ISO 7932), sulphite-reducing Clostridia (ISO 7937), yeasts and moulds (ISO 21527-1), and the presence in 25 g of Salmonella spp. (ISO 6579). On the same samples, the presence of undesired ingredients, which can be identified as remnants of packaging materials, was evaluated by two different methods: stereomicroscopy according to published methods; and stereomicroscopy coupled with a computer vision system (IRIS Visual Analyzer VA400). All FFPs analysed were safe from a microbiological point of view. TVC was limited and Salmonella was always absent. When remnants of packaging materials were considered, the contamination level was below 0.08% (w/w). Of note, packaging remnants were found mainly from the 1-mm sieve mesh fractions. Finally, the innovative computer vision system demonstrated the possibility of rapid detection for the presence of packaging remnants in FFPs when combined with a stereomicroscope. In conclusion, the FFPs analysed in the present study can be considered safe, even though some improvements in FFP processing in the feeding plant can be useful in further reducing their microbial loads and impurity. Graphical Abstract: